Talisman and Sudan: the role of multinationals in conflict zones - Fisher, Colin (Henry Stewart Talks, 2017)
The case study looks at the actions of Talisman, an oil company working in Sudan during the civil war with the south (now South Sudan), and the pressure it was under to end its involvement in that country. It asks whether the role of multinationals in conflict zones might be more ambiguous than we might imagine.